Comparison of consumer complaint behaviour in the online and offline retail environment in Singapore. - Chia, Xinyi. (2008)
Although there is vast research done on defining Consumer Complaint Behaviour (CCB), the attention has been focused on it being in the offline shopping environment. The inherent features of online retailing, such as the lack of physical presence of products and the overall environment of perceived insecurity on the Internet, may mean that the current CCB model is not applicable and transferable to the online environment. Therefore this study attempts to fill the gap in research done on complaint behaviour by exploring differences in CCB between online and offline environments in the context of consumers in Singapore. A recall-based questionnaire was designed to survey independent samples of online and offline shoppers about their previous dissatisfying shopping experiences. A total of 155 responses were gathered from students from local universities and polytechnics. Results show that no significant differences were found between CCB in online versus offline retail environments in Singapore. However, results also show that if online shoppers are supplied with more complaint channels online, they will be more willing to voice their complaints to the retailers. This implies that online retailers should provide their customers with more complaint channels, including real-time chat systems that offer synchronized communication with consumers.